Case Study: Online Learning for Design and Calculation of Machines - Queiruga-Dios, Araceli; Izard-Anaya, Eulalia; Bullón-Pérez, Juan José; Hernández-Encinas, Ascensión; Martín-Vaquero, Jesús (Frontiers in ICT, 2015)
In recent years, the University of Salamanca together with other 45 European universities have changed our university qualifications, resulting in substantial changes in the system of education. In this case study we detail the particular case of the subject of Design and Calculation of Machines of the Degree in Mechanical Engineering, which is given at the School of Industrial Engineering at the University of Salamanca. The use of technological tools and resources to make students acquire the desired competences suppose a change in the learning paradigm. The more traditional teaching system changes to become a self-learning system. With the files, tasks, and activities available on the web platform, students could follow their own learning. We include data related to the improvements in the students’ marks.